Evaluation of the perception of learning of functional orofacial exploration in paediatric patients - Sánchez - Sánchez, Esperanza (2020)
It was assessed the perception of improvement in the knowledge in functional orofacial exploration after its explanation and practical demonstration to dentistry students. A questionnaire was administered to 63 students containing questions on functional exploration and the students’ ability to perform it. Groups of 10 students were randomly established and an experienced teacher explained the procedure. Two weeks later, the students completed the same questionnaire. Changes in performance were evaluated using the chi-square test, whereas the relationships between some questions were determined using the kappa statistic. All variables in the questionnaires showed a significant improvement between the first and second questionnaires except the question regarding finger sucking, where there were no important changes. In general terms, before the practical explanation in small groups, 54,8% knew how to perform an orofacial functional exploration. At the end of the study, the percentage rose to 86,3%. The methodology proposed in our study improves students’ perception of their ability to perform a functional exploration in paediatric patients. The most unknown areas were the centric relation, lip sucking and palpation of the masticatory muscles, and the best-known one was the exploration of the type of breathing.